Holistic face processing is influenced by non‐conscious visual information. (9th July 2021) - Jin, Haiyang; Oxner, Matt; Corballis, Paul M.; Hayward, William G.
Abstract : Holistic face processing has been widely implicated in conscious face perception. Yet, little is known about whether holistic face processing occurs when faces are processed unconsciously. The present study used the composite face task and continuous flash suppression (CFS) to inspect whether the processing of target facial information (the top half of a face) is influenced by irrelevant information (the bottom half) that is presented unconsciously. Results of multiple experiments showed that the composite effect was observed in both monocular and CFS conditions, providing the first evidence that the processing of top facial halves is influenced by the aligned bottom halves no matter whether they are presented consciously or unconsciously. However, much of the composite effect for faces without masking was disrupted when bottom facial parts were rendered with CFS. These results suggest that holistic face processing can occur unconsciously, but also highlight the significance of holistic processing of consciously presented faces.